A Review of Nigerian Christians’ Response to the 2019 Witchcraft Conference - Egodi Uchendu (Eastern African Journal of Humanities and Social Sciences)
For centuries, witchcraft was a major part of religious belief in many cultures, including those in Africa. It was the focus of the much-contested conference of the University of Nigeria, Nsukka, in 2019. Many Nigerian Christians publicly debated the relevance of a conference on witchcraft and demanded its cancellation. This paper is a personal contemplation of the reactions of Nigerian Christians to the conference. Data for the paper is drawn from interviews, newspaper publications and the social media. I argue that an academic study of witchcraft is not out of tune with any religious creed, including Christianity; and that the vehemence against the conference by the Christian community in Nigeria, to which I belong, calls into question our understanding of our faith. In effect, the paper probes the public reaction to the conference, considers its unintended outcomes, and draws out the lessons that can be learned about Nigerian Christians and Christianity in Nigeria.